Derecho y desarrollo agrario y su incidencia en el principio constitucional del buen vivir - Dávila Moreira, Israel Alberto (2016)
This legal research work entitled "Law and development agrarian and his incidence in the principle constitutional of the good life", is a transcendental subject of individual and collective manner that links many subjects that are fighting for their land and for the right to use it because they are dispossessed class; but the land redistribution has many changes in models of ownership affecting the peasant sector. Conflicts of society through access to productive resources of the Earth generated the subjects claim for recognition and regularization of land tenure to ensure the permanence and productive reproduction in their rural possessions; where the ownership of domain or property can be recognized by supporting under the standards in the regulations of the civil code and the agrarian legislation, providing solutions to the problems of securitization, legalization, resolution of internal and external conflicts which may have access to credit, training, technical advisories, among many other advantages that ensure the good living of each individual